2016
DOI: 10.1128/aac.00693-15
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Antituberculosis Drugs and Their Effect on Tuberculosis Treatment Outcome

Abstract: Therapeutic drug monitoring in tuberculosis remains controversial. We evaluated the relationship between antituberculosis drug levels in blood and clinical outcome. Serum concentrations of first-line antituberculosis drugs were measured in tuberculosis patients between March 2006 and April 2013. Venous blood was drawn 2 h after drug ingestion and was analyzed using highperformance liquid chromatography-tandem mass spectrometry. We retrospectively reviewed the data and determined the association of serum drug l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 22 publications
4
48
0
Order By: Relevance
“…For example, Chideya et al [76] reported that patients with inadequate PZA levels in serum (adjusted for HIV status and CD4 + T cell counts) were at three times greater risk for poor outcome compared to patients with normal concentrations of PZA. However, data collected by Park et al [79] indicated that low serum concentrations of isoniazid rather than PZA had a slight association with TB recurrence and drug resistance.…”
Section: Pza and The Host Environmentmentioning
confidence: 95%
“…For example, Chideya et al [76] reported that patients with inadequate PZA levels in serum (adjusted for HIV status and CD4 + T cell counts) were at three times greater risk for poor outcome compared to patients with normal concentrations of PZA. However, data collected by Park et al [79] indicated that low serum concentrations of isoniazid rather than PZA had a slight association with TB recurrence and drug resistance.…”
Section: Pza and The Host Environmentmentioning
confidence: 95%
“… 5 Several authors have found that low anti-TB drug concentrations (pyrazinamide, rifampicin and isoniazid) were associated with poor TB treatment outcomes 7 13 19 20 while others did not. 8 21 22 Many of these studies were retrospective with small sample sizes and only a few included patients with HIV infection. This is an aspect that this study will explore further and contribute to the existing studies by providing prospectively collected data with a considerably large sample size including a population of severely immunosuppressed patients coinfected with TB/HIV who at a particularly high risk of poor TB treatment outcomes.…”
Section: Findings To Datementioning
confidence: 99%
“…6 On the other hand, the low level of isoniazid led to the drug resistance of M. tuberculosis and poor outcomes of TB-treatment. 7,8 Thus, scanty and controversy information is available on the association between isoniazid serum concentrations, treatment efficacy and toxicity. 9…”
Section: Introductionmentioning
confidence: 99%